2020
DOI: 10.1101/2020.03.23.003269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A disordered encounter complex is central to the yeast Abp1p SH3 domain binding pathway

Abstract: Protein-protein interactions are involved in a wide range of cell processes. These interactions often involve intrinsically disordered proteins (IDPs) and protein binding domains.However, the details of IDP binding pathways are hard to characterize using experimental approaches that cannot always capture low populations of intermediate states. SH3 domains are common protein interaction domains that typically bind proline-rich disordered segments and are involved in cell signaling, regulation, and assembly. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 88 publications
0
1
0
Order By: Relevance
“…[2] In addition, soon after arriving at Skidmore, Aurelia started a new collaboration with Prof. Elliott Stollar at the University of Liverpool to study binding of disordered protein segments to SH3 domains, and many students in her lab have joined this project and made significant progress on different aspects of the project (which is now funded by an NSF-Research in Undergraduate Institutions (RUI) grant) based on their individual expertise. [3] For example, one student who joined the lab was a computer science minor, so Aurelia assigned her to figure out how to use a Python package that creates Markov State Models for molecular dynamics simulations, which could then be applied to the protein binding simulations on which other students in the lab were working. In one case, after a student showed that he could work very independently on his initial project, Aurelia asked him to take over a project working on trying to simulate cis-trans isomerization of a proline residue within an intrinsically disordered protein.…”
Section: Designing Student Projectsmentioning
confidence: 99%
“…[2] In addition, soon after arriving at Skidmore, Aurelia started a new collaboration with Prof. Elliott Stollar at the University of Liverpool to study binding of disordered protein segments to SH3 domains, and many students in her lab have joined this project and made significant progress on different aspects of the project (which is now funded by an NSF-Research in Undergraduate Institutions (RUI) grant) based on their individual expertise. [3] For example, one student who joined the lab was a computer science minor, so Aurelia assigned her to figure out how to use a Python package that creates Markov State Models for molecular dynamics simulations, which could then be applied to the protein binding simulations on which other students in the lab were working. In one case, after a student showed that he could work very independently on his initial project, Aurelia asked him to take over a project working on trying to simulate cis-trans isomerization of a proline residue within an intrinsically disordered protein.…”
Section: Designing Student Projectsmentioning
confidence: 99%